May the Force Not Be With You During Culture: Eliminating Mechano-Associated Feedback During Culture Preserves Cultured Atrial and Pacemaker Cell Functions - Kirschner Peretz, Noa; Segal, Sofia; Yaniv, Yael (Frontiers in Physiology, 2020)
Cultured cardiomyocytes have been shown to possess significant potential as a model for characterization of mechano-Ca2+, mechano-electric, and mechano-metabolic feedbacks in the heart. However, the majority of cultured cardiomyocytes exhibit impaired electrical, mechanical, biochemical and metabolic functions. More specifically, the cells do not beat spontaneously or beat at a rate far lower than their physiological counterparts (pacemaker cells), and self-oscillate (atrial and ventricular cells) in culture. Thus, efforts are being invested to ensure that cultured cardiomyocytes maintain the shape and function of freshly isolated cells. Elimination of contraction during culture has been shown to preserve mechano-Ca2+, mechano-electric, and mechano-metabolic feedback loops of cultured cells. This review focuses on pacemaker cells, which reside in the sinoatrial node (SAN) and generate the regular heartbeat through initiation of the heart's electrical, metabolic and biochemical activities. In parallel, it places emphasis on atrial cells, which are responsible for bridging the electrical conductance from the SAN to the ventricle. The review provides a summary of the main mechanisms responsible for mechano-electrical, Ca2+ and metabolic feedback in pacemaker and atrial cells and of culture methods existing for both cell types. The work concludes with an explanation of how elimination of mechano-electrical, mechano-Ca2+ and mechano-metabolic feedbacks during culture result in sustained cultured cell function.